2009
DOI: 10.1177/1753193408097324
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Rotational Malunions of the Distal Radius: The Role of Pure Derotational Osteotomy

Abstract: Sagittal rotational malunion after distal radius fractures was identified in eight patients by the presence of a "hinge" point on the volar cortex on the lateral radiograph, and the ulnar head being shorter than the anterior lip of the radius on the posterior-anterior radiograph. The surgical correction consisted of preplating the distal fragment with a volar locking plate before an osteotomy through the "hinge" point, and correcting the dorsal tilt of the distal fragment. Any dorsal defect was filled with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Furthermore, since there is minimal extensor tendon irritation, removal of implants is not a necessity, in contrast to dorsal plating. The overall results in this series are comparable with, if not superior to, the results of similar studies (Capo et al, 2010; Del Piñal et al, 2009; Henry, 2007; Malone et al, 2006; Miyake et al, 2011; Ozer et al, 2011; Peterson et al, 2008; Prommersberger et al, 2002; Wada et al, 2011). Satisfactory improvement in clinical symptoms has been achieved and good bone union occurs with the use of morsellized bone graft and rigid internal fixation, despite early functional use after treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, since there is minimal extensor tendon irritation, removal of implants is not a necessity, in contrast to dorsal plating. The overall results in this series are comparable with, if not superior to, the results of similar studies (Capo et al, 2010; Del Piñal et al, 2009; Henry, 2007; Malone et al, 2006; Miyake et al, 2011; Ozer et al, 2011; Peterson et al, 2008; Prommersberger et al, 2002; Wada et al, 2011). Satisfactory improvement in clinical symptoms has been achieved and good bone union occurs with the use of morsellized bone graft and rigid internal fixation, despite early functional use after treatment.…”
Section: Discussionsupporting
confidence: 86%
“…This article describes a less invasive technique for a dorsal single-cut open-wedge osteotomy, to correct an extrarticular rotational malunion of the distal radius (Del Piñal et al, 2009). Malunions requiring significant radial lengthening (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, during corrective osteotomy, the radial angle may be spontaneously reduced after correction of the dorsal tilt deformity (Figure 7B). Del Piñal et al described such a malunion as sagittal rotational malunion , which can be restored anatomically by pure derotational osteotomy only in the sagittal plane (Del Piñal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…von Campe et al stated that 47% of patients showed a residual shortening deformity of ≥ 2 mm after a procedure comprising systematic pre-operative planning using plain radiographs (von Campe et al, 2006). Del Piñal et al also stated that ulnar variance improved by 3 mm after derotational osteotomy in the sagittal plane, without lengthening of sagittal rotational malunion (Del Piñal et al, 2009). Therefore, we considered that ulnar variance has less accuracy for the planning of corrective osteotomy compared with 3D evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient cohort, 25% of patients had only dorsal tilt deformity, which meant that complex reconstruction was unnecessary. Derotational osteotomy only in the sagittal plane can correct the deformity in these patients (Del Piñal et al, 2009; Henry, 2007).…”
Section: Discussionmentioning
confidence: 99%